Pembuatan User Interface Aplikasi Berbasis Website K-Foodies - Rachmadina Nabila Nelson; Siti Chodidjah; Deasy Indayanti; Santi Widianti; Iwan Setiadi (Universitas Katolik Widya Karya Malang, 2023)
The User Interface (UI) of the website-based application 'K-Foodies' was created to provide information on Korean street food recipes with an attractive appearance and is easy to use. In the context of the popularity of Korean street food in Jakarta and people's interest in cooking themselves, the difficulty in finding scattered recipe information is an obstacle. Creating the UI involved using Figma software, with a focus on UI design and user experience. The UI design includes descriptions of Korean street food, recipes, and cooking steps. Usability tests using the completion rate method will measure the effectiveness of the UI based on user interactions with the system in the form of various task scenarios. The aim of this research is to create an attractive and easy-to-use UI for the 'K-Foodies' application, allowing users to easily find Korean street food recipes in one place.